Buildings on Kongsbakken, near Parkgata in Tromsø,Norway ... - Campbell, Sandy (University of Alberta Library, 2024)
These buildings were across the road from Kings Park in Tromsø, Norway. The building in the foreground is older. It has orange exterior paneling and a peaked grey slate roof. It also has a narrow black on white banner that reads, "It's never too late to be a rock star." It also has two types of windows - vertical sash-type windows and diamond shaped feature windows. The building to the right is painted in three sections, white to the right, dark gold and pale yellow. The middle section has a rooftop patio. The building in the background is a modern apartment style building with a flat roof, rectangular windows and balconies. ...